Moda e economia criativa: políticas culturais no Brasil contemporâneo - Heloisa Helena de Oliveira Santos (Universidade do Vale do Rio dos Sinos (UNISINOS), 2014)
As demonstrated by some authors who reflect on contemporary cultural policies in Brazil, the country finds itself in a unique moment with regard to the relationship between cul- ture and the state. In this sense, the Ministry of Culture (MinC) is much more active and involved in discussions about the development of Brazilian society. This role acquired by MinC is recent and is inserted into the broader PT government program, initiated in 2003. As a result of this new place assumed by this ministry, it proposed to review not only its performance, but also the areas that would compose its scope and could be included in its political project. This reflection led to a rapprochement with the discussions taking place at the international and especially supranational level – centrally in the agencies associated with the United Nations – on the creative economy: the area has gained ground in Brazil and sectors which hitherto were not considered as part of national cultural poli- cies became part of them. So in this article I want to briefly address the appropriations made by the Brazilian government of the discussions held by UNCTAD/UN, as well as to discuss how MinC understands the fashion in this context, further indicating some of the actions carried out not only by political leaders, but also by the actors involved in the sector to affirm this new position of fashion as a target of cultural policies in Brazil.